2004
DOI: 10.1111/j.1365-2591.2004.00867.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of electrochemically activated water as an irrigant in an infected tooth model

Abstract: All but two groups (AA and C) were significantly different from their PBS controls. There was a significant difference between the C/NA groups with and without ultrasonication but not between other combinations. NA (U) and AA (U) were the most effective test solutions but NaOCl (3%) gave by far the highest bacterial kills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 27 publications
1
63
0
8
Order By: Relevance
“…Despite different denominations, they are all oxidizing solutions containing hypochlorous acid and produced according to the same principles, i.e., by passing a saline solution over titanium-coated electrodes. These solutions have been assessed for their ability to remove debris and smear layer from root canals (13,14) and eliminate bacteria (12,15). Studies have found favorable results and biocompatibility with vital tissues (14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite different denominations, they are all oxidizing solutions containing hypochlorous acid and produced according to the same principles, i.e., by passing a saline solution over titanium-coated electrodes. These solutions have been assessed for their ability to remove debris and smear layer from root canals (13,14) and eliminate bacteria (12,15). Studies have found favorable results and biocompatibility with vital tissues (14).…”
Section: Introductionmentioning
confidence: 99%
“…Due to limitations of NaOCl, especially in relation to toxicity, the use of irrigants known as "electrochemically activated water" (12,13), "oxidative potential water" (14) or "super-oxidized water" (15,16) has been suggested in the literature. Despite different denominations, they are all oxidizing solutions containing hypochlorous acid and produced according to the same principles, i.e., by passing a saline solution over titanium-coated electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…A comparative study by Gulabivala et al, in 2004, found that bacterial culture study for CFU showed the hydroxyl ions in ECA water reduce the biofilm formed by E. faecalis in infected tooth models [18].…”
Section: Discussionmentioning
confidence: 99%
“…(17) Since then iodine has been shown to be bactericidal, fungicidal, tuberculocidal, virucidal and sporicidal.…”
Section: Iodinementioning
confidence: 99%
“…(17) It is thought that iodine attacks key group proteins, nucleotides and fatty acids, leading to cell death.…”
Section: Iodinementioning
confidence: 99%